Cryptanalysis Of Block Ciphers: Generalization, Extensions And Integration - Phan, Raphael Chung Wei (2005)
This thesis is about the crytanalysis of block ciphers, and is organized into 3 parts : Generalization, Extensions and Integrations. Our main position is that one should view block cipher cryptanalysis as an interelation of many techniques and not just one in isolation, e.g. slightly changing the properties of one would result in another; and that cipher security should be considered with respect to the environment which they are used in relation to other primitives.